Lithium iron phosphate positive electrode material with high-rate cycle performance

By using chitosan, citric acid and graphene oxide to form a carbon cladding layer with a network structure, the problem of low electronic conductivity of LiFePO4 positive electrode material is solved, and the high-rate cycling and electrochemical performance is improved.

CN119230806AActive Publication Date: 2024-12-31HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD

Patent Information

Application Number
CN202411778023.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2024-12-31
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The electronic conductivity of LiFePO4 positive electrode material is low, resulting in a significant increase in the impedance of the positive electrode material during the high-ratio cycle, affecting the power performance of the battery.

Method used

Chitosan, citric acid and graphene oxide are used as carbon sources to form a gel with a network structure through amidation reaction, and calcined under a reducing atmosphere to form a nuclear body of lithium iron phosphate and reduced graphene oxide/carbon coating layer. The positive electrode material is composed to improve the uniformity and density of the coating and provide continuous electron migration channels.

Benefits of technology

By improving the uniformity and density of carbon coating, the impedance of the positive electrode material is reduced, and the high-speed cycle performance and electrochemical performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a lithium iron phosphate positive electrode material with high-rate cycle performance, and belongs to the technical field of lithium batteries, the lithium iron phosphate positive electrode material provided by the invention comprises a lithium iron phosphate core body and a reduced graphene oxide / carbon coating layer, the reduced graphene oxide / carbon coating layer combines chitosan, citric acid and graphene oxide as a carbon source, and the carbon source is a carbon source. And forming gel with a cross-linked network structure under the action of glutaraldehyde, and calcining in a reducing atmosphere to obtain a coating layer. According to the lithium iron phosphate positive electrode material prepared by a sol-gel method, the coating is uniform, complete and compact by utilizing the synergistic effect of the chitosan, the citric acid and the graphene oxide, a continuous electron migration channel can be provided, the impedance of the positive electrode material is reduced during high-rate circulation, and the electrochemical performance of the positive electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium iron phosphate positive electrode material with high rate cycle performance. Background Art

[0002] LiFePO4 with an olivine structure can reversibly insert and extract lithium ions, and its theoretical specific capacity is 170 mAh g -1 , with a voltage platform of 3.5V, and the raw material source is abundant, non-toxic, and environmentally friendly, so it is considered to be an ideal positive electrode material for lithium-ion batteries. However, in the LiFePO4 structure, the common vertices of FeO6 octahedrons are separated by PO4 tetrahedrons, and there is no continuous FeO6 common edge octahedron network, which cannot form an electronic conductor. The conduction of electrons can only be carried out through Fe-O-Fe, which makes the electronic conductivity of LiFePO4 low, only 10 -9 S / cm. During the high-rate charge and discharge process of LiFePO4, the impedance of the positive electrode material increases significantly, resulting in increased power loss of the battery and poor performance in high-rate cycle performance.

[0003] In view of the disadvantage of low electronic conductivity of LiFePO4, researchers have made a lot of efforts, and the method adopted is mainly surface coating. Carbon coating is a method that has been studied more and industrialized in the surface coating of LiFePO4. Carbon materials have good conductivity and are low in price. There are generally two ways to carbon coating: one is to mix carbon powder with raw materials in a certain proportion and then calcine at high temperature; the other is to add carbon-containing organic matter to the precursor of LiFePO4, and then react at high temperature to form LiFePO4 while forming a carbon coating layer on its surface. However, the carbon coating prepared by the general method has problems of uneven coating and loose carbon layer. The performance of the carbon-coated positive electrode material actually prepared still needs to be further improved. Summary of the invention

[0004] The purpose of the present invention is to provide a lithium iron phosphate positive electrode material with high rate cycle performance, and to improve the high rate cycle performance of the lithium iron phosphate positive electrode material by improving the uniformity and compactness of the carbon coating.

[0005] The purpose of the present invention can be achieved through the following technical solutions: The present invention provides a lithium iron phosphate positive electrode material with high rate cycle performance. The lithium iron phosphate positive electrode material comprises a lithium iron phosphate core and a reduced graphene oxide / carbon coating layer, and the chemical formula is LiFePO4@C / RGO, wherein the lithium iron phosphate is the core and the reduced graphene oxide / carbon is the coating layer; The steps for preparing the lithium iron phosphate positive electrode material are as follows: Step 1: dissolving chitosan in acetic acid solution to form a CS solution, dissolving citric acid in water to form a CA solution, and adding graphene oxide to deionized water for ultrasonic dispersion to form a GO dispersion; Step 2: Mix the CS solution, CA solution and GO dispersion to form a CS-CA-GO material mixed solution, and adjust the pH to 6-7 with sodium hydroxide; Step 3: Mix the lithium source, iron source and phosphoric acid according to Li, Fe and PO4 3- The molar ratio is 1.0-1.1:1.0:1.0, and the mixture is added to anhydrous ethanol to obtain a slurry, and the CS-CA-GO material mixed solution is added and stirred for 10 minutes, and a glutaraldehyde aqueous solution is added, and a wet gel is formed after heating and stirring. Step 4: Heat the wet gel to remove the solvent to form a dry gel, place it in a vacuum drying oven to dry it to obtain a precursor, place the precursor in a tubular atmosphere furnace, calcine it under a nitrogen atmosphere, cool it to room temperature, and then grind and sieve it to obtain a lithium iron phosphate positive electrode material.

[0006] Furthermore, in the step 1, the volume fraction of the acetic acid solution is 1-3%, and the amount of chitosan added to the CS solution is 2-3.5wt%.

[0007] Furthermore, in the step 1, the dosage of citric acid in the CA solution is 0.5-3wt%.

[0008] Furthermore, the concentration of graphene oxide in the GO dispersion is 1-5 mg / mL.

[0009] Furthermore, in the CS-CA-GO material mixed solution, the CS solution, the CA solution and the GO dispersion are mixed according to a mass ratio of chitosan, citric acid and graphene oxide of 10:1-1.4:0.1-0.3.

[0010] Furthermore, the lithium source is one of lithium carbonate and lithium hydroxide monohydrate, the iron source is one of ferrous chloride tetrahydrate and ferrous sulfate heptahydrate, and the total mass concentration of the lithium source, the iron source and phosphoric acid added to anhydrous ethanol is 20-30%.

[0011] Furthermore, the volume ratio of the CS-CA-GO material mixed solution and the slurry is 0.8-2.0:1.

[0012] Furthermore, the mass concentration of the glutaraldehyde aqueous solution is 15-25%, the dosage of the glutaraldehyde aqueous solution is 10-20% of the volume of the CS-CA-GO material mixed solution, the temperature of the heating and stirring reaction is 50-60° C., and the reaction time is 2-4 hours.

[0013] Furthermore, the temperature for heating to remove the solvent is 90-100°C, the vacuum drying oven drying temperature is 100-120°C, the drying time is 12-24h, and the heating setting for calcination is: first heating to 350-400°C and keeping the temperature constant for 6-8h, then heating to 600-750°C and keeping the temperature constant for 10-12h.

[0014] Beneficial effects of the present invention: Chitosan, citric acid and graphene oxide are used as carbon sources. The carboxyl groups on graphene oxide and citric acid react with the amino groups in the chitosan structure to form amide bonds. After mixing with the positive electrode material, a gel with a network structure is obtained. After calcination under a reducing atmosphere, a positive electrode material consisting of a lithium iron phosphate core and a reduced graphene oxide / carbon coating layer is obtained. By adding reduced graphene oxide, the low conductivity defect of amorphous carbon formed by organic carbon sources is compensated, and the cross-linking effect between chitosan, citric acid and graphene oxide in the presence of glutaraldehyde is utilized to make the coating uniform, complete and dense, providing a continuous electron migration channel, reducing the impedance of the positive electrode material during high-rate cycling, and improving the electrochemical performance of the positive electrode material. DETAILED DESCRIPTION

[0015] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] Example 1 Step 1: weigh chitosan at a mass fraction of 3.5 wt% and dissolve it in a 2% volume fraction acetic acid solution to form a CS solution; weigh citric acid at a mass fraction of 0.5 wt% and dissolve it in water to form a CA solution; weigh graphene oxide at a concentration of 1 mg / mL and add it to deionized water for ultrasonic dispersion for 10 min to form a GO dispersion; Step 2: Stir and mix the CS solution, CA solution and GO dispersion for 30 minutes according to the mass ratio of chitosan, citric acid and graphene oxide of 10:1:0.1 to obtain a CS-CA-GO material mixed solution, and adjust the pH to 6-7 with sodium hydroxide; Step 3: Lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid are mixed according to the ratio of Li, Fe and PO4 3-The molar ratio is 1.0:1.0:1.0, and the total mass fraction of lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid added to the anhydrous ethanol is 20%. After mixing, a slurry is obtained. The CS-CA-GO material mixed solution and the slurry are mixed and stirred for 10 minutes at a volume ratio of 0.8:1. Then, a 25% mass fraction of glutaraldehyde aqueous solution is added, and the amount of glutaraldehyde aqueous solution added is 10% of the volume of the CS-CA-GO material mixed solution. The temperature is raised to 60°C and stirred for 2 hours to form a wet gel. Step 4: Heat the wet gel at 90°C to evaporate and remove the solvent to form a dry gel, place it in a vacuum drying oven at 100°C and dry it for 12 hours to obtain a precursor, place the precursor in a tubular atmosphere furnace, and calcine it in a nitrogen atmosphere, first heating to 350°C and keeping the temperature constant for 6 hours, then heating to 750°C and keeping the temperature constant for 12 hours, cool to room temperature, and then grind and sieve to obtain lithium iron phosphate positive electrode material.

[0017] Example 2 The difference from Example 1 is that in step 2, the CS solution, CA solution and GO dispersion are stirred and mixed according to the mass ratio of chitosan, citric acid and graphene oxide of 10:1.2:0.1, and the other steps and conditions are the same as in Example 1.

[0018] Example 3 The difference from Example 1 is that in step 2, the CS solution, CA solution and GO dispersion are stirred and mixed according to the mass ratio of chitosan, citric acid and graphene oxide of 10:1.4:0.1, and the other steps and conditions are the same as in Example 1.

[0019] Example 4 The difference from Example 1 is that in step 2, the CS solution, CA solution and GO dispersion are stirred and mixed according to the mass ratio of chitosan, citric acid and graphene oxide of 10:1.2:0.2, and the other steps and conditions are the same as in Example 1.

[0020] Example 5 The difference from Example 1 is that in step 2, the CS solution, CA solution and GO dispersion are stirred and mixed according to the mass ratio of chitosan, citric acid and graphene oxide of 10:1.2:0.3, and the other steps and conditions are the same as in Example 1.

[0021] Example 6 The difference from Example 1 is that in step 3, lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid are prepared according to the ratio of Li, Fe and PO4 3- The molar ratio is 1.05:1.0:1.0 and added to anhydrous ethanol. The other steps and conditions are the same as in Example 1.

[0022] Example 7 The difference from Example 1 is that in step 3, lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid are prepared according to the ratio of Li, Fe and PO4 3- The molar ratio is 1.1:1.0:1.0 and added to anhydrous ethanol. The other steps and conditions are the same as in Example 1.

[0023] Example 8 The difference from Example 1 is that in step 3, the total mass fraction of lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid added to anhydrous ethanol is 25%, the CS-CA-GO mixed solution and the slurry are mixed and stirred at a volume ratio of 1.4:1, and the other steps and conditions are the same as in Example 1.

[0024] Example 9 The difference from Example 1 is that in step 3, the total mass fraction of lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid added to anhydrous ethanol is 30%, the CS-CA-GO material mixed solution and slurry are mixed and stirred at a volume ratio of 2.0:1, and the other steps and conditions are the same as in Example 1.

[0025] Comparative Example 1 Compared with Example 1, the difference of this comparative example is that graphene oxide is not added to the coating layer material. The specific steps are as follows: Step 1: weigh chitosan at a mass fraction of 3.5 wt% and dissolve it in a 2% by volume acetic acid solution to form a CS solution; weigh citric acid at a mass fraction of 0.5 wt% and dissolve it in water to form a CA solution; Step 2: Mix the CS solution and the CA solution at a mass ratio of chitosan to citric acid of 10:1 for 30 minutes to obtain a CS-CA material mixed solution, and adjust the pH to 6-7 with sodium hydroxide; Step 3: Lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid are mixed according to the ratio of Li, Fe and PO4 3- The molar ratio is 1.0:1.0:1.0, and the total mass fraction of lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid added to the anhydrous ethanol is 20%. The slurry is obtained after mixing. The CS-CA material mixed solution and the slurry are mixed and stirred for 10 minutes at a volume ratio of 0.8:1. Then, a 25% mass fraction of glutaraldehyde aqueous solution is added, and the amount of glutaraldehyde aqueous solution added is 10% of the volume of the CS-CA material mixed solution. The temperature is raised to 60°C and stirred for 2 hours to form a wet gel. Step 4: Heat the wet gel at 90°C to evaporate and remove the solvent to form a dry gel, place it in a vacuum drying oven at 100°C and dry it for 12 hours to obtain a precursor, place the precursor in a tubular atmosphere furnace, and calcine it in a nitrogen atmosphere, first heating to 350°C and keeping the temperature constant for 6 hours, then heating to 750°C and keeping the temperature constant for 12 hours, cool to room temperature, and then grind and sieve to obtain lithium iron phosphate positive electrode material.

[0026] Comparative Example 2 Compared with Example 1, the difference of this comparative example is that chitosan is not added to the coating layer material. The specific steps are as follows: Step 1: Weigh 8.0 wt% of citric acid and dissolve it in water to form a CA solution, weigh graphene oxide at a concentration of 1 mg / mL, add it to deionized water and ultrasonically disperse it for 10 minutes to form a GO dispersion; Step 2: CA solution and GO dispersion were stirred and mixed for 30 minutes according to the mass ratio of citric acid to graphene oxide of 10:0.1 to obtain a CA-GO material mixed solution, and the pH was adjusted to 6-7 with sodium hydroxide; Step 3: Lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid are mixed according to the ratio of Li, Fe and PO4 3- The molar ratio is 1.0:1.0:1.0, and the total mass fraction of lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid added to anhydrous ethanol is 20%. After mixing, a slurry is obtained. The CA-GO material mixed solution and the slurry are mixed and stirred for 10 minutes at a volume ratio of 0.8:1. Then, a 25% mass fraction of glutaraldehyde aqueous solution is added, and the amount of glutaraldehyde aqueous solution added is 10% of the volume of the CA-GO material mixed solution. The temperature is raised to 60°C and stirred for 2 hours to form a wet gel. Step 4: Heat the wet gel at 90°C to evaporate and remove the solvent to form a dry gel, place it in a vacuum drying oven at 100°C and dry it for 12 hours to obtain a precursor, place the precursor in a tubular atmosphere furnace, and calcine it in a nitrogen atmosphere, first heating to 350°C and keeping the temperature constant for 6 hours, then heating to 750°C and keeping the temperature constant for 12 hours, cool to room temperature, and then grind and sieve to obtain lithium iron phosphate positive electrode material.

[0027] Comparative Example 3 Compared with Example 1, the difference of this comparative example is that no citric acid is added to the coating layer material. The specific steps are as follows: Step 1: weigh chitosan at a mass fraction of 3.5 wt% and dissolve it in an acetic acid solution with a volume fraction of 2% to form a CS solution; weigh graphene oxide at a concentration of 1 mg / mL and add it to deionized water for ultrasonic dispersion for 10 min to form a GO dispersion; Step 2: Stir and mix the CS solution and the GO dispersion for 30 minutes at a mass ratio of chitosan to graphene oxide of 10:0.1 to obtain a CS-GO mixed solution, and adjust the pH to 6-7 with sodium hydroxide; Step 3: Lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid are mixed according to the ratio of Li, Fe and PO4 3-The molar ratio is 1.0:1.0:1.0, and the total mass fraction of lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid added to the anhydrous ethanol is 20%. The slurry is obtained after mixing. The CS-GO mixed solution and the slurry are mixed and stirred for 10 minutes at a volume ratio of 1.2:1. Then, a 25% mass fraction of glutaraldehyde aqueous solution is added, and the amount of glutaraldehyde aqueous solution added is 10% of the volume of the CS-GO mixed solution. The temperature is raised to 60°C and stirred for 2 hours to form a wet gel. Step 4: Heat the wet gel at 90°C to evaporate and remove the solvent to form a dry gel, and place it in a vacuum drying oven at 100°C for 12 hours to obtain a precursor. Place the precursor in a tubular atmosphere furnace and calcine it under a nitrogen atmosphere. First, heat it to 350°C and keep it at a constant temperature for 6 hours, then heat it to 750°C and keep it at a constant temperature for 12 hours. After cooling to room temperature, grind and sieve to obtain LiFePO4@C / RGO material.

[0028] Comparative Example 4 Compared with Example 1, the difference of this comparative example is that chitosan and graphene oxide are not added to the coating layer material. The specific steps are as follows: Step 1, weighing citric acid according to a mass fraction of 8.0wt% and dissolving it in water to form a CA solution; Step 2: Lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid are mixed according to the ratio of Li, Fe and PO4 3- The molar ratio is 1.0:1.0:1.0, wherein the total mass fraction of lithium carbonate, ferrous chloride tetrahydrate and phosphoric acid added to the anhydrous ethanol is 20%, and the mixture is mixed to obtain a slurry, and the CA solution and the slurry are mixed and stirred for 10 minutes at a volume ratio of 0.8:1, and then stirred for 2 hours and allowed to stand to form a wet gel; Step 3: Heat the wet gel at 90°C to evaporate and remove the solvent to form a dry gel, and place it in a vacuum drying oven at 100°C for 12 hours to obtain a precursor. Place the precursor in a tubular atmosphere furnace and calcine it under a nitrogen atmosphere. First, heat it to 350°C and keep it constant for 6 hours, then heat it to 750°C and keep it constant for 12 hours. After cooling to room temperature, grind and sieve to obtain LiFePO4@C material.

[0029] The performance of the positive electrode materials prepared in Examples 1 to 9 and Comparative Examples 1 to 4 was tested with reference to GB / T 33822-2017 "Nano-lithium iron phosphate" standard. The results are shown in Table 1:

[0030] As can be seen from Table 1, the proportion of citric acid in the carbon source is gradually increased in Examples 1 to 3, and the discharge specific capacity of the positive electrode material is slightly improved. Among them, in Example 3, due to the relatively low carbon content of citric acid, increasing the proportion of citric acid will reduce the carbon content in the positive electrode material, resulting in a decrease in electrochemical performance compared with Example 2. Examples 4 and 5 increase the proportion of graphene oxide on the basis of Example 2. Compared with the amorphous carbon obtained by calcining chitosan and citric acid, graphene has better conductivity. The discharge specific capacity of the positive electrode material prepared in Example 5 at 0.1C reaches 165.0mAh / g. In Examples 6-9, the element ratio of the positive electrode material and the concentration of the slurry are adjusted, and the obtained positive electrode material has good electrochemical properties. Combined with Comparative Examples 1-4, compared with Example 1, the three materials as carbon sources will affect the cycle performance of the lithium iron phosphate positive electrode material, and the cycle performance of the positive electrode material of the comparative example is poor, among which the cycle capacity retention rate of Comparative Example 4 is the lowest.

[0031] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0032] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A lithium iron phosphate positive electrode material with high rate cycle performance, characterized in that: The lithium iron phosphate positive electrode material comprises a lithium iron phosphate core and a reduced graphene oxide / carbon coating layer, and the chemical formula is LiFePO4@C / RGO, wherein the lithium iron phosphate is the core and the reduced graphene oxide / carbon is the coating layer; The steps for preparing the lithium iron phosphate positive electrode material are as follows: Step 1: dissolving chitosan in acetic acid solution to form a CS solution, dissolving citric acid in water to form a CA solution, and adding graphene oxide to deionized water for ultrasonic dispersion to form a GO dispersion; Step 2: Mix the CS solution, CA solution and GO dispersion to form a CS-CA-GO material mixed solution, and adjust the pH to 6-7 with sodium hydroxide; Step 3: Mix the lithium source, iron source and phosphoric acid according to Li, Fe and PO4 3- The molar ratio is 1.0-1.1:1.0:1.0, and the mixture is added to anhydrous ethanol to obtain a slurry, and the CS-CA-GO material mixed solution is added and stirred for 10 minutes, and a glutaraldehyde aqueous solution is added, and a wet gel is formed after heating and stirring. Step 4: Heat the wet gel to remove the solvent to form a dry gel, place it in a vacuum drying oven to dry it to obtain a precursor, place the precursor in a tubular atmosphere furnace, calcine it under a nitrogen atmosphere, cool it to room temperature, and then grind and sieve it to obtain a lithium iron phosphate positive electrode material.

2. The lithium iron phosphate positive electrode material with high rate cycle performance according to claim 1, characterized in that: In the step 1, the volume fraction of the acetic acid solution is 1-3%, and the amount of chitosan added to the CS solution is 2-3.5wt%.

3. The lithium iron phosphate positive electrode material with high rate cycle performance according to claim 1, characterized in that: In the step 1, the dosage of citric acid in the CA solution is 0.5-3wt%.

4. The lithium iron phosphate positive electrode material with high rate cycle performance according to claim 1, characterized in that: The concentration of graphene oxide in the GO dispersion is 1-5 mg / mL.

5. The lithium iron phosphate positive electrode material with high rate cycle performance according to claim 1, characterized in that: In the CS-CA-GO material mixed solution, the CS solution, the CA solution and the GO dispersion are mixed according to the mass ratio of chitosan, citric acid and graphene oxide of 10:1-1.4:0.1-0.

3.

6. The lithium iron phosphate positive electrode material with high rate cycle performance according to claim 1, characterized in that: The lithium source is one of lithium carbonate and lithium hydroxide monohydrate, the iron source is one of ferrous chloride tetrahydrate and ferrous sulfate heptahydrate, and the total mass concentration of the lithium source, the iron source and phosphoric acid added to anhydrous ethanol is 20-30%.

7. The lithium iron phosphate positive electrode material with high rate cycle performance according to claim 1, characterized in that: The volume ratio of the CS-CA-GO material mixed solution to the slurry is 0.8-2.0:

1.

8. The lithium iron phosphate positive electrode material with high rate cycle performance according to claim 1, characterized in that: The mass concentration of the glutaraldehyde aqueous solution is 15-25%, the dosage of the glutaraldehyde aqueous solution is 10-20% of the volume of the CS-CA-GO material mixed solution, the temperature of the heating and stirring reaction is 50-60° C., and the reaction time is 2-4 hours.

9. The lithium iron phosphate positive electrode material with high rate cycle performance according to claim 1, characterized in that: The temperature for heating to remove the solvent is 90-100°C, the drying temperature in the vacuum drying oven is 100-120°C, the drying time is 12-24h, and the heating setting for calcination is: first heating to 350-400°C and keeping the temperature constant for 6-8h, then heating to 600-750°C and keeping the temperature constant for 10-12h.

Citation Information

Patent Citations

  • Preparation method of high-rate lithium iron manganese phosphate positive electrode material and lithium battery

    CN118929618A

  • METHOD FOR PREPARING GRAPHENE-BASED LiFePO4 / C COMPOSITE MATERIAL

    US20150102267A1

  • Positive electrode active material, method for the preparation thereof, positive electrode plate, secondary battery and electrical device containing the same

    US20240332515A1

Cited By

  • Graphene-coated lithium iron phosphate positive electrode material and preparation method thereof

    CN119841298A

  • Nanometer spherical shell type lithium iron phosphate composite positive electrode material and preparation method thereof

    CN121054674A